Energy balance‐related factors in childhood and adolescence and risk of colorectal cancer based on KRAS, PIK3CA, and BRAF mutations and MMR status. Issue 12 (30th September 2022) - Jenniskens, Josien C. A.; Offermans, Kelly; Simons, Colinda C. J. M.; Samarska, Iryna; Fazzi, Gregorio E.; van der Meer, Jaleesa R. M.; Smits, Kim M.; Schouten, Leo J.; Weijenberg, Matty P.; Grabsch, Heike I.; van den Brandt, Piet A.
Abstract: KRAS mutations ( KRAS mut ), PIK3CA mut, BRAF mut, and deficient DNA mismatch repair (dMMR) have been associated with the Warburg effect. We previously reported differential associations between early‐life energy balance‐related factors (height, energy restriction, body mass index [BMI]) and colorectal cancer (CRC) subtypes based on the Warburg effect. We now investigated associations of early‐life energy balance‐related factors and the risk of CRC subgroups based on mutation and MMR status. Data from the Netherlands Cohort Study was used. KRAS mut, PIK3CA mut, BRAF mut, and MMR status were available for 2349 CRC cases, and complete covariate data for 1934 cases and 3911 subcohort members. Multivariable‐adjusted Cox regression was used to estimate associations of height, energy restriction proxies (exposure to Dutch Hunger Winter, Second World War, Economic Depression), and early adult BMI (age 20 years) with risk of CRC based on individual molecular features and combinations thereof (all‐wild‐type+MMR‐proficient [pMMR]; any‐mutation/dMMR). Height was positively associated with any‐mutation/dMMR CRC but not all‐wild‐type+pMMR CRC, with the exception of rectal cancer in men, and with heterogeneity in associations observed for colon cancer in men ( p ‐heterogeneity = 0.049) and rectal cancer in women ( p ‐heterogeneity = 0.014). Results on early‐life energy restriction proxies in relation to the risk of CRC subgroups did not show clear patterns. Early adult BMI was positively, but not significantly, associated with KRAS mut colon cancer in men and with BRAF mut and dMMR colon cancer in women. Our results suggest a role of KRAS mut, PIK3CA mut, BRAF mut, and dMMR in the etiological pathway between height and CRC risk. KRAS mut might potentially play a role in associations of early adult BMI with colon cancer risk in men, and BRAF mut and dMMR in women.